Synergy Mechanisms of AI-Powered Cross-Domain Value Co-Creation: A Literature Synthesis (2022-2026) - Yi, Fan (International Journal of Multidisciplinary Research, 2026)
Artificial intelligence (AI) has evolved from domain-specific applications to a catalyst for cross-sector value co-creation, enabling interdisciplinary collaboration across healthcare, quantum science, digital commerce, cybersecurity, and finance. This paper synthesizes 10 recent studies (2022-2026) to explore three core synergy mechanisms driving AI-powered cross-domain innovation: technological convergence through hybrid architectures, trust-enabled data sharing via privacy-enhancing technologies (PETs), and ecosystem collaboration supported by inclusive AI frameworks. By analyzing how these mechanisms unlock complementary resources and capabilities across sectors, the review reveals that effective synergy relies on balancing domain specificity with interoperability, compliance with innovation, and scalability with accessibility. The findings provide a framework for understanding how AI fosters cross-domain value co-creation, offering implications for researchers designing collaborative AI systems and practitioners seeking to leverage interdisciplinary innovation.